Polymerized-Type I Collagen Downregulates Inflammation and Improves Clinical Outcomes in Patients with Symptomatic Knee Osteoarthritis Following Arthroscopic Lavage: A Randomized, Double-Blind, and Placebo-Controlled Clinical Trial - Janette Furuzawa-Carballeda; Guadalupe Lima; Luis Llorente; Carlos Nuñez-Álvarez; Blanca H. Ruiz-Ordaz; Santiago Echevarría-Zuno; Virgilio Hernández-Cuevas (The Scientific World Journal)
Objectives. Polymerized-type I collagen (polymerized collagen) is a downmodulator of inflammation and cartilage regenerator biodrug. Aim. To evaluate the effect of intraarticular injections of polymerized collagen after arthroscopic lavage on inflammation and clinical improvement in patients with knee osteoarthritis (OA). Methods. Patients (n=19) were treated with 6 intraarticular injections of 2 mL of polymerized collagen (n=10) or 2 mL of placebo (n=9) during 3 months. Followup was 3 months. The primary endpoints included Lequesne index, pain on a visual analogue scale (VAS), WOMAC, analgesic usage, the number of Tregs and proinflammatory/anti-inflammatory cytokine-expressing peripheral cells. Secondary outcomes were Likert score and drug evaluation. Clinical and immunological improvement was determined if the decrease in pain exceeds 20 mm on a VAS, 20% of clinical outcomes, and inflammatory parameters from baseline. Urinary levels of C-terminal crosslinking telopeptide of collagen type II (CTXII) and erythrocyte sedimentation rate (ESR) were determined. Results. Polymerized collagen was safe and well tolerated. Patients had a statistically significant improvement (P<0.05) from baseline versus polymerized collagen and versus placebo at 6 months on Lequesne index, VAS, ESR, Tregs IL-1β, and IL-10 peripheral-expressing cells. Urinary levels of CTXII were decreased 44% in polymerized collagen versus placebo. No differences were found on incidence of adverse events between groups. Conclusion. Polymerized collagen is safe and effective on downregulation of inflammation in patients with knee OA.